2022
DOI: 10.1039/d1dt04203c
|View full text |Cite
|
Sign up to set email alerts
|

B–O–B bridged BOPPY derivatives: synthesis, structures, and acid-catalyzed cistrans isomeric interconversion

Abstract: A new class of BOPPY derivatives has been facilely synthesized by a two-step reaction of coupling 3,5-dimethylpyrrole-2-carbaldehyde with 2,3-dihydrazinoquinoxaline (QDH) followed by coordinating with BF3·OEt2. The reaction mainly produces a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Owing to the important advantages above, the asymmetrical bisboron-anchoring BOPPY chromophore quickly attracted some attention as advantageous photophysical properties above and promising frameworks for building blocks and functional materials. [47][48][49][50] For example, in 2022, Ono and coworkers 47 reported a new family of BOPPY dimers as flag-hinge chromophores starting from the pre-modified diformyl-2,2'bipyrroles, which manifest good multicolor and circularly polarized emission. Shen and coworkers 48 developed B-O-B bridged BOPPY dimers by reacting 3,5-dimethylpyrrole-2carbaldehyde with 2,3-dihydrazinoquinoxaline, and following boron complex.…”
Section: Synthesis and Properties Of Benzo-fused Boppys From Isoindolesmentioning
confidence: 99%
“…Owing to the important advantages above, the asymmetrical bisboron-anchoring BOPPY chromophore quickly attracted some attention as advantageous photophysical properties above and promising frameworks for building blocks and functional materials. [47][48][49][50] For example, in 2022, Ono and coworkers 47 reported a new family of BOPPY dimers as flag-hinge chromophores starting from the pre-modified diformyl-2,2'bipyrroles, which manifest good multicolor and circularly polarized emission. Shen and coworkers 48 developed B-O-B bridged BOPPY dimers by reacting 3,5-dimethylpyrrole-2carbaldehyde with 2,3-dihydrazinoquinoxaline, and following boron complex.…”
Section: Synthesis and Properties Of Benzo-fused Boppys From Isoindolesmentioning
confidence: 99%
“…For example, Ono 45 reported a series of BOPPY dimers from diformyl-2,2′bipyrroles as flag-hinge chromophores exhibiting multicolor and circularly polarized luminescence. Shen 46 developed B− O−B bridged BOPPY dimers by coupling 3,5-dimethylpyrrole-2-carbaldehyde with 2,3-dihydrazinoquinoxaline and found that the two diastereomeric isomers under weak acid could undergo feasible cis−trans interconversion owing to the acidcatalyzed B−N bond cleavage. Stark 47 developed novel BOPPY-based fluorescent dopamine D2 and D3 receptor ligands, which demonstrate relatively large Stokes shifts and provide versatile possibility for amine coupling.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Fluorophores BODIPY, BOPHY, BOPPY and boranil, etc., which contain NÀ BÀ N, OÀ BÀ O or NÀ BÀ O bridges have been widely investigated because of their outstanding photophysical properties such as tunable emission, high fluorescent quantum yields, and high stability. [1][2][3][4][5][6][7][8][9] Unlike conventional N,N and O,Obidentate organic boron complexes, N,O-bidentate boron complexes, which can be prepared by B-coordination using the ligands 2-(pyridin-2-yl)phenol and its analogues, have only been developed in recent years. The low-symmetry or asymmetric structure of these N,O-bidentate boron complexes gives them unique photophysical properties such as a relatively large Stokes shift, [10][11][12][13][14][15][16][17][18][19] strong emission in solution and/or solid, [14,16,17,[20][21][22][23][24][25][26][27][28][29] NIR absorption and emission, [20,30,31] and anion sensing.…”
Section: Introductionmentioning
confidence: 99%
“…[34] The second one, which was synthesized from ortho-hydroxylated substrates and pyrrole in one step (Scheme 1 (5)(6)), is applied as a probe for detecting H + and F À ions. [35] The last one was prepared by condensation, oxidation and coordination reactions from aldehydes and pyrrole (Scheme 1 (7)(8)(9)). [36] Thus, the development of diverse sevenmembered N,O-bidentate organic difluroboron complexes is still an area for researchers to explore.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation